FREQUENCY ASSESSMENT OF EMERGENCE OF EXTENSIVELY DRUG RESISTANT SALMONELLA TYPHI STRAINS IN QUETTA, BALOCHISTAN - Nasir, Shafia; Asif, Naveed; Nasir, Oroosa; Arif, Sunila Tashfeen; Azam, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objectives: To determine frequency of multidrug resistant (MDR) and extensive drug resistant (XDR) strains of Salmonella typhi (S. typhi) and Salmonella paratyphi (S. paratyphi) in Quetta, Balochistan of PakistanStudy Design: Descriptive Cross-SectionalPlace and Duration: Department of Microbiology, CMH Quetta, Pakistan. from March 2019 to March 2020Materials and Methods: A total of 2760 (n) suspected cases of typhoid fever, irrespective of age and gender, reporting at the hospital in this duration and underwent blood culture. Isolates were cultured and identified using standard microbiological procedures. Antimicrobial sensitivity against typhoidal Salmonellae was determined using Kirby-Bauer disc diffusion method as per the guidelines of Clinical and Laboratory Standards Institute (2018) and all the XDR isolates were confirmed by Vitek 2 system.   Results: A total of 173 (6.3%) cultures showed positive results. with mean age of 18.9 ± 11.1 years, out of which 136 (78.6%) were male and 37 (21.1%) were female patients. Antibiotic susceptibility results showed that 166 (96%) of isolates were S. typhi. MDR strains were observed in 104(60.1%) and XDR strains were observed in 81 (46.8%) cases.Conclusion:  A significant proportion of S. typhi isolates from confirmed cases of enteric fever demonstrated MDR (60.1%) and XDR (46.8%) strains in Quetta, Balochistan. We recommend empiric therapy with azithromycin in patients with uncomplicated and therapy with carbapenem for complicated cases of enteric fever acquired in Karachi or Quetta. Large scale population-based studies are recommended to get better information about antibiotic susceptibility pattern of S. typhi and S. paratyphi in other areas.